The politics of non-communicable diseases in the global South. (May 2016) - Reubi, David; Herrick, Clare; Brown, Tim
Abstract: In this paper, we explore the emergence of non-communicable diseases (NCDs) as an object of political concern in and for countries of the global South. While epidemiologists and public health practitioners and scholars have long expressed concern with the changing global distribution of the burden of NCDs, it is only in more recent years that the aetiology, politics and consequences of these shifts have become an object of critical social scientific enquiry. These shifts mark the starting point for this special issue on 'The Politics of NCDs in the Global South' and act as the basis for new, critical interventions in how we understand NCDs. In this paper, we aim not only to introduce and contextualise the six contributions that form this special issue, but also to identify and explore three themes – problematisation, care and culture – that index the main areas of analytical and empirical concern that have motivated analyses of NCDs in the global South and are central to critical engagement with their political contours.